Audit Risk Assessment and Fair Financial Reporting: Evidence from Muscat Stock Exchange in Oman (Jurnal Cendekia Keuangan, 2026)
Introduction/Main Objectives: This study examines the link between audit risk assessment and the fairness of financial statements among companies listed on the Muscat Stock Exchange. It highlights auditors' perceptions of risk assessment covering inherent, control, and detection risks and underscores its importance for stakeholders and boards in supporting sound financial decisions and mitigating financial distress, losses, and bankruptcy, in line with international guidelines such as ISO 31000. Novelty: This study addresses the gap in audit risk assessment research within the Omani context. By applying advanced quantitative analysis, it demonstrates the importance of risk assessment in safeguarding firm assets and preventing bankruptcy or shutdown, while offering a foundation for future studies. Research Methods: This study employs a deductive quantitative approach using structured questionnaires distributed to external auditors and stockholders. Of 250 questionnaires, 162 valid responses were analyzed with SPSS to test the hypotheses. Finding/Results: Findings reveal a significant positive association between audit risk assessment and the fairness of financial statements, which strengthens stakeholder trust in Oman's financial reporting. Conclusion: This study confirms a significant positive relationship between audit risk assessment and the fairness of financial statements, reinforcing the reliability of external auditors' reports in Oman. Supported by regulatory frameworks and Oman's Vision 2040 emphasis on governance and transparency, the findings highlight the crucial role of auditors in enhancing stakeholder confidence in financial reporting.